The effect of perceptual training on the learning of english vowels by brazilian portuguese speakers - Oliveira, Denize Nobre (2007)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.